2004
DOI: 10.1042/bj20040389
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of three novel members of the Arabidopsis thaliana equilibrative nucleoside transporter (ENT) family

Abstract: Research on metabolism of nucleotides and their derivatives has gained increasing interest in the recent past. This includes de novo synthesis, analysis of salvage pathways, breakdown and transport of nucleotides, nucleosides and nucleobases. To perform a further step towards the analysis of nucleoside transport in Arabidopsis, we incubated leaf discs with various radioactively labelled nucleosides. Leaf cells imported labelled nucleosides and incorporated these compounds into RNA, but not into DNA. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 41 publications
7
96
0
Order By: Relevance
“…The measured maximal activities for UK and UPRT were unchanged in the mutants generated in the course of this work (see Supplemental Figure 2 online). It has to be mentioned that the activities for both enzymes are severalfold in excess compared with uptake rates of uridine (Wormit et al, 2004;Traub et al, 2007). However, it cannot be excluded that the cosubstrate of UPRT phosphoribosyl pyrophosphate limits uracil salvage as mutants in phosphoribosyl pyrophosphate synthesis showed that this metabolite may colimit growth rates in Arabidopsis (Koslowsky et al, 2008).…”
Section: Altered Nucleosidase Activity Effects Uridine Degradation Nmentioning
confidence: 99%
“…The measured maximal activities for UK and UPRT were unchanged in the mutants generated in the course of this work (see Supplemental Figure 2 online). It has to be mentioned that the activities for both enzymes are severalfold in excess compared with uptake rates of uridine (Wormit et al, 2004;Traub et al, 2007). However, it cannot be excluded that the cosubstrate of UPRT phosphoribosyl pyrophosphate limits uracil salvage as mutants in phosphoribosyl pyrophosphate synthesis showed that this metabolite may colimit growth rates in Arabidopsis (Koslowsky et al, 2008).…”
Section: Altered Nucleosidase Activity Effects Uridine Degradation Nmentioning
confidence: 99%
“…None of the 12 identified Arabidopsis NAT loci are yet functionally characterized. Equilibrative nucleoside transporters (ENT) found in plants, protozoans and mammals, act primarily as nucleoside transporters but can also transport nucleobases adenine, guanine, xanthine and hypoxanthine or cytokinin [7][8][9][10][11][12][13]. Eight identified ENT loci are present in the Arabidopsis genome.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant AtENT1 expressed in yeast cells has been found to transport adenosine, guanosine, and cytidine in a pH-dependent manner [10,18]. However, it has been suggested that AtENT1 may not transport uridine based on competition assay [10], although uridine is efficiently transported by most ENT proteins characterized to date [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that AtENT1 may not transport uridine based on competition assay [10], although uridine is efficiently transported by most ENT proteins characterized to date [19,20]. The recombinant proteins of AtENTs 3, 4, 6, and 7 have all been found to transport adenosine, guanosine, cytidine, and uridine in a facilitative manner [17,18]. In contrast, the yeast-expressed AtENT8 is unable to mediate the uptake of any of the four nucleosides (adenosine, guanosine, cytidine, and uridine) tested so far [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation